Penyebaran Agama Islam Di Surabaya = The Eshtablishment of Muslims Bases in Surabaya - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT The early islamization process in Indonesia, in particular in East Java has been being debated. Many Scholars have conducted research on it in order to reveal its secret. Their findings have been very beneficial to throw light on it for the further researchers. One of them is a grave of a Muslim of 1082 AD, whose name is Fatimah, the daughter of Maimun in Leran (near to Gresik), wich signifies the existence of muslim people in Gresik. Through Gresik, Islam was spred to Surabaya by the ulamas of Gresik and Giri. Nevertheless, Islam obtained its significant momentum after the coming of Sunan Ampel to Surabaya. In round the fifteenth century, he with his disciples and companions spred Islam in Surabaya and its surroundings. He established a traditional-Islamic school and a mosque in Kembang Kuning and Ampel. Furthermore, he made Ampel his base. The efforts led to the establishment of the bases of muslim in Surabaya namely both in Kembang Kuning and Ampel and in Kemayoran and Kepanjen. Besides the mentioned factors, the spreading of Islam to Surabaya could not separated from the existence of Surabaya its self, which by the time became one of the most important anchorages. Due to its rule, many foreigners such as Chineses, Indians, Arabs, etc came there for their both business and religions affairs - to spread Islam. Some of them lived there. This research is aimed to describe the islamization process and the establishment of the bases of muslims in Surabaya. This research is considered important due to the fact that Surabaya was the centre of the spreading of Islam in Java, and was the harbor and the strategic trade center as well. This indicates that is difficult to separate the spreading of a religion from economic factors even though other factors are also important. By under- standing the islamization process in Surabaya, the way by which the early process of islamization went in Indonesia can be generally understood in spite of local studies that have own uniques and are influenced by there onw socio-historical scope.